Impact assessment of uterine artery embolization on reproductive - N. A. Kalinina; A. N. Sulima; Z. S. Rumyantseva; P. N. Baskakov; V. D. Kalinin (IRBIS LLC, 2023)
Introduction. Uterine artery embolization (UAE) is an effective minimally invasive manipulation that has been widely applied in obstetric and gynecological practice. The expediency of using this method of surgical treatment in patients with reproductive plans is still controversial. The main clinicians' concerns are the risk of developing local endometrial ischemia able to lead to habitual miscarriage, premature birth and pathological placentation as well as decreased ovarian reserve due to impaired adequate ovarian blood supply.Aim: to analyze the literature data regarding UAE effect on reproductive function.Materials and Methods. The search for literature was carried out in databases Web of Science, eLibrary, Scopus, PubMed/MEDLINE. We selected articles for the years 1995-2023 devoted to assessing UAE influence on reproductive function. The articles were searched by the keywords "embolization", "uterine arteries", "reproductive function", "prognosis", "assessment". No methodological filter was used to exclude the omission of suitable articles. The study included full-text sources and literary reviews on the subject under study. Articles that are not directly related to the subject UAE were excluded from the review. In order to avoid the inclusion of duplicate publications if two same author studies were found, the study period of each author was assessed, and if publication dates coincided, the most recent publication was selected.Results. Based on the review of domestic and foreign literature sources over recent years, it can be concluded that there are restrictions on the frequency and outcomes of pregnancy in such cohort of patients who underwent UAE. Many patients included in existing studies and case reports have variable factors complicating direct analysis or comparison such as age of patients, previous spontaneous abortions, previous uterine surgery, different techniques and professional training of X-ray endovascular surgeons, uncertainty of a woman regarding further reproductive plans and other forms of infertility, which can also distort research results. In addition, the most well-controlled studies often have small patients sample sizes not allowing to obtain meaningful clinical information from thereof.Conclusion. Pregnancy is possible in women after UAE, and many of these pregnancies proceed without complications and lead to successful childbirth. The actual fertility rate after UAE remains uncertain, but is approaching 38.3 % based on the available published results.